Lateral nasal wall haemangioma in a young female: a rare case - Ansari, Ashfaque; Nair, Sanjana U. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Hemangiomas are benign tumours originating from vascular structures in the body. Histologically they are divided into capillary, cavernous and mixed types. Although it is very commonly seen in head and neck region, it is very rarely seen in the nasal cavity, nasopharynx and paranasal sinuses and it accounts for only 10% of all head and neck haemangiomas. In this patient the haemangioma was seen arising from the lateral nasal wall, of the right nasal cavity. So far in the literature very few such cases have been reported till date.